The moral economy of guanxi and the market of corruption: Networks, brokers and corruption in China$1 (Bs courtss - Li, Ling (2018)
In this article, I offer an economic analysis of the characteristics that are associated with corruption when it is facilitated through social exchange or guanxi as it is called in China. To that end, I challenge the framework applied in classic social exchange theories and contend that social exchange can be better distinguished from market exchange based on whether the intention to exchange is concealed and not based on the exchanging parties$1 (Bsubjective reflections on the nature and outlook of their exchange relationship. I also identify that corruption participants rely on a self-executable operating mechanism to facilitate negotiation and enforcement of exchange terms instead of the informal reputational system that is used in ordinary social exchange. In addition, I explain how the involvement of professional brokers democratizes guanxi-based corruption and extends the otherwise privileged exchange opportunities to those beyond the guanxi networks with lowered cost. - Reproduced.s
Keywords: Courts - China